PENINGKATAN PENJUALAN KERIPIK PISANG SETELAH MEMPEROLEH SERTIFIKAT HALAL SERTA PERILAKU KONSUMENNYA DI KOTA BANDAR LAMPUNG - Elsa Fitriana; Yaktiworo Indriani; Begem Viantimala (Lampung University, 2020)
This study aims to study the halal certification process of banana processed products at the Institute forFood, Drugs, and Cosmetics Studies of The Indonesian Ulama Council (LPPOM MUI) Lampung Provinceto find out the increase in sales of banana chips after obtaining a halal certificate, and to explore consumer behavior of Lampung banana chips branded KPS, PD. AS, and KPKK. The research is conducted by surveymethod. Data collection was conducted in March 2019 in which 45 people were selected by using accidentalsampling. The data are analyzed by descriptive analysis and Attitude model of Multiatribute Fishbein. Thehalal certification process carried out by LPPOM MUI Lampung Province on banana chips agroindusty hasseveral online steps on web regs.e-lppommui.org. The increase in sales after obtaining a halal certificate is an increase in the number of production with the turnover reaching 40 percent. When purchasing bananachips, halal is highly considered by consumers. Consumers at KPS, PD. AS, and KPKK are satisfied andmay repurchase.Key words: banana chips, consumers, halal certificate